The Relationship Between Family Support and Elderly Behavior in Hypertension Control in the Working Area of Tiga Balata Health Center - Hendri Kurniawan; Br Sinukaban, Evita Dora (International Journal of Public Health Excellence (IJPHE), 2023)
Support from family and friends is needed in the management of people with hypertension. The family is a support system in the life of people with hypertension, so that their condition does not get worse and avoid complications due to hypertension. The purpose of this study was to determine the relationship between family support and the behavior of the elderly in controlling hypertension at Tiga Balata Health Center, Simalungun Regency. This study uses a quantitative method, this type of research is analytic with a cross sectional approach. The population of this study were 33 hypertensive patients at Tiga Balata Health Center. The sample of this research is 33 respondents. Most of the elderly have good family support as many as 17 respondents (52.8%). And most of the elderly have good behavior as many as 20 respondents (60.6%). Chi-square test results with a significance level of 0.05 indicate that the p value is 0.000 ± 0.05, meaning H, it is accepted that there is a relationship between family support and elderly behavior in controlling hypertension at Tiga Balata Health Center, Simalungun Regency. The result of Chi Square 0.573 is positive, which means that the poorer the family support, the lower the behavior of the elderly. Good family support with good elderly behavior 14 respondents (87.5%) and good family support with bad elderly behavior 2 respondents (12.5%), poor family support with good elderly behavior 3 respondents (17.6%) and family support not good with the behavior of the elderly is not good 14 respondents (82.4%). The behavior of the elderly in controlling hypertension must at least be accompanied by a good family and also good motivation from the family.